Experimental investigation on drag reduction of flowing crop suspensions of the pulp fibers in circular pipe heat exchanger. (18th May 2020) - Ahmed, Syed Muzamil; Kazi, Salim Newaz; Khan, Ghullamullah; Akram, Naveed; Dahari, Mahidzal; Zubir, Mohd Nashrul Mohd; Ahmad, Pervaiz; Zaharinie, Tuan
Abstract: Pressure drop measurements were obtained for different kenaf bast pulp fiber suspensions flowing through a circular pipe heat exchanger test loop. The data were generated from the flow loop over a selected range of flow rates and fiber concentrations. It was found that the magnitude of the pressure drop of the kenaf bast fiber suspensions is dependent on the characteristics, concentration, and pulping method of fibers. Considerable drag reduction is obtained for concentrations of 0.6 mass% at high flow rates. Such a reduction of pressure drop is significant for the design and optimization of crop fiber handling equipment and the relevant piping systems. Furthermore, the effects of various fiber processing techniques, fiber properties, and flexibility on pressure drop were studied in relation to the influence on fiber suspension properties.